Challenges in Measuring Online Advertising Systems - Guha, Saikat; Cheng, Bin; Francis, Paul (Proceedings of Internet Measurement Conference (IMC), 2010)
Online advertising supports many Internet services, such as search, email, and social networks. At the same time, there are widespread concerns about the privacy loss associated with user targeting. Yet, very little is publicly known about how ad networks operate, especially with regard to how they use user information to target users. This paper takes a first principled look at measurement methodologies for ad networks. It proposes new metrics that are robust to the high levels of noise inherent in ad distribution, identifies measurement pitfalls and artifacts, and provides mitigation strategies. It also presents an analysis of how three different classes of advertising — search, contextual, and social networks, use user profile information today.